2014
DOI: 10.3324/haematol.2014.117846
|View full text |Cite
|
Sign up to set email alerts
|

Radotinib in the treatment of chronic phase chronic myeloid leukemia patients

Abstract: We read with interest the article by Kim et al. 1 in which the authors provided the efficacy and safety data of radotinib (IY5511HCL), an oral BCR-ABL1-specific 2 nd generation tyrosine kinase inhibitor (TKI), in 77 patients with chronic phase-chronic myeloid leukemia (CP-CML) in a multinational phase II trial. After a median duration of radotinib exposure of approximately 12 months and a median follow up of 23.4 months, the complete cytogenetic response (CCyR) rate was 47% by 12 months, and the overall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Ghalesardi et al showed that the ratio of male to female was higher in the b2a2 group compared to b3a2 [19] . In a Mexican study, a higher leukocyte count in patients with the b2a2 transcript was reported [20] . However, in our patients, hyperleukocytosis ≥ 100 × 10⁹/L was found to be more associated with the b3a2 transcript type without statistically significant results, which is consistent with other studies [21] .…”
Section: Discussionmentioning
confidence: 93%
“…Ghalesardi et al showed that the ratio of male to female was higher in the b2a2 group compared to b3a2 [19] . In a Mexican study, a higher leukocyte count in patients with the b2a2 transcript was reported [20] . However, in our patients, hyperleukocytosis ≥ 100 × 10⁹/L was found to be more associated with the b3a2 transcript type without statistically significant results, which is consistent with other studies [21] .…”
Section: Discussionmentioning
confidence: 93%
“…Overall survival (OS) and progression-free survival (PFS) rates at 12 months were 96% and 86%, respectively. However, radotinib has not been evaluated in patients failing 2GTKI [ 31 ].…”
Section: Approved Treatment Optionsmentioning
confidence: 99%
“…Overall radotinib discontinuation rates both in the original study 8 and in the 24-month update 17 were also comparable to other studies as concluded by Kim and colleagues. 18 Relatively higher rates of AEs and biochemical abnormalities of radotinib in the salvage setting raised some concerns, 19 and the authors concluded that as a starting dose the current 800 mg daily dose may be appropriate in the second-line setting, but the dose for frontline administration should be reduced; studies were ongoing for further dose optimization. 18 Radotinib in newly diagnosed patients with CML-CP Prior to the utilization of radotinib in the context of first-line therapy, there were some 2GTKIs tested in the frontline treatment of patients with CML-CP.…”
Section: Pre-clinical and Clinical Activities Of Radotinibmentioning
confidence: 99%
“…Relatively higher rates of AEs and biochemical abnormalities of radotinib in the salvage setting raised some concerns, 19 and the authors concluded that as a starting dose the current 800 mg daily dose may be appropriate in the second-line setting, but the dose for frontline administration should be reduced; studies were ongoing for further dose optimization. 18…”
Section: Radotinibmentioning
confidence: 99%